Analisis hasil pewarna alami kayu secang pada serat selulosa - Kurniati Kurniati; Asiani Abu (Seminar Nasional LP2M UNM, 2019)
Color variations are needed to support the development of the textile industry to increase the attractiveness of a product. Based on the sources obtained, textile dyes are divided into 2, namely natural and synthetic dyes. Natural dyes can be the best solution to replace synthetic dyes that can be harmful to the environment. One of the natural dyes that can be used as natural dyes is the secang wood. This study aims to determine how the processing of the secang wood into the secang extract and the strength of fabric absorption and color sharpness produced on cellulose fibers, proteins and synthesis of the coloring process using secang wood using alum, quicklime and tunjung fixator. The procedure of this research was carried out starting from literature review, observation, verification of data, experimentation, and processing of research results. Processing data in this study using descriptive statistical analysis. The results showed that the extraction process of secang wood included cutting small or shredding secang wood, weighing 500 grams of secang wood then cooking with 2 liters of water, cooking until the water shrank to 1 liter so it was ready to be used as natural dyes. The ability to absorb cotton cloth (cellulose fibers) against extract secang using a fixator produces sharp or strong colors but is dull and less even on the surface of the fabric.